Rehabilitación de un caso con periodontitis activa y periimplantitis avanzada. Enfoque mínimamente invasivo. - Anitua, Eduardo (2022)
Periodontal disease (PD) is an oral pathology with a high prevalence worldwide. There are different treatments for periodontal disease, with the trend in recent years being towards minimally invasive treatments. In cases where implants cannot be treated predictably in the long term, we should also consider removing the implant using atraumatic methods and retreatment of the case. A point to be taken into account both for the insertion of a dental implant and for its maintenance afterperiimplantitis or for its replacement is the periodontal status of the patient. Periodontal disease can affect the prognosis of our treatment in this type of situation. In the following clinical case, we show the treatment of a patient affected by PD and periimplantitis with a minimally invasive approach.